Characterization of the testicular transcriptome of transgenic rat overexpressing regucalcin: insights into (in)fertility - Santos, Vanessa Sofia Mesquita (2018)
Regucalcin (RGN) is a highly-conserved calcium (Ca2+)-binding protein, which was initially identified in the rat liver, playing a role in intracellular Ca2+ homeostasis. Over the last years, RGN was identified in several non-reproductive and reproductive tissues and, due to its modulation of Ca2+ levels, and regulation of Ca2+-dependent and -independent enzymes, the panoply of RGN known functions has been widening. RGN has thus also been involved in the regulation of intracellular signaling pathways, oxidative stress and metabolism, as well as important biological processes such as cell proliferation and apoptosis. RGN is encoded by the Rgn gene, identified as an androgen-target gene broadly expressed in all testicular cell types, which for the first linked RGN with male reproduction. More recently, transgenic rats overexpressing RGN (Tg-RGN) have been shown to display increased sperm viability with lower incidence of tail defects, as well as resistance to oxidative stress and to chemical- or radiation-induced apoptosis. Despite the different evidences supporting the beneficial role of RGN in spermatogenesis, the molecular players underlying its actions are not yet known. The present study aimed to identify the pathways and molecular players underlying the cytoprotective actions of RGN in spermatogenesis. For this purpose, the testicular transcriptome of Tg-RGN rats compared to wild-type (Wt) rats was analyzed using an RNA sequencing approach (RNA-seq). Differentially expressed genes were clustered according to their expression pattern, gene ontology (GO) and pathway enrichment analysis. A total of 1064 genes were differentially expressed in the Tg-RGN rats with higher enrichment scores found for GO terms for biological processes such as ion transport or meiotic cell cycle. The obtained information was then filtered considering fold-change, expression level and the potential relevance for spermatogenesis, and 10 genes were selected for real-time quantitative reverse transcription polymerase chain reaction (qPCR) validation of the RNA-seq results. Atp10b, Orai1, Sfrp2 and Tnni1 genes were validated as being up-regulated genes in the testis of Tg-RGN rats, whereas Fign and Sycp1 genes were down-regulated, which suggests their likely role as RGN partners in modulating spermatogenesis. Afterwards, the expression of the 10 selected genes in different types of testicular cells was investigated. For this purpose, a cell line with spermatogonia stem cell characteristics (GC-6spg cells) and primary Sertoli Cells (SCs) isolated from Wt rats were used. Gene expression was assessed by reverse transcription PCR (RT-PCR). All differentially expressed genes, with the exception of Atp10b, were expressed in SCs; Eng, Fign, Orai1, Star, Sycp1 and Tnni1 genes were also detected in GC-6spg cells. Overall, the findings obtained in the present thesis gave a new insight into the molecular mechanisms behind RGN’ actions in the testes and provided the basis for future research exploring and deepening the knowledge about the role of RGN in the regulation of spermatogenesis and male (in)fertility.